Pendidikan Kesehatan Media Audio Visual Lebih Efektif untuk Meningkatkan Pengetahuan Siswa tentang Kesehatan Reproduksi - Regina, Esa Rara; Delima, Rosa (Universitas Jenderal Achmad Yani Yogyakarta, 2013)
Background: Statistical data of 2008 in Indonesia showed from 43,3 million adolescents aged 15-24 years of unhealthy behavior, teenage Indonesia from 23 million aged 15-24 years, 83,3% had had sexual intercourse. Negative behavior patterns and risk of adolescent reproductive health will have an impact on their future, so it requires a special education discuss reproductive health. Audiovisual media and the leaflet is a medium that can be used in the delivery of reproductive health education information. Preliminary study of the 5 people from 216 students in grade VII showed that students did not know about health reproductive. Objectives: This study aims to determine the ratio of health ducation via media audio visual and leaflets to students' knowledge about health reproductive adolescent in SMP Negeri 2 Ampel Boyolali. Methods: The method in this study was quasi-experimental (quasi experiment) and the use of design Non Equivalent Pre-Post Design. Samples were taken by technique proportional random sampling is a class VII student at SMPl 2 Ampel Boyolali much as 140 people. The instruments of the study questionnaire and test results were analyzed with Wilcoxon Signed Ranks Test and the Kolmogorov- Smirnow. Results: Knowledge of students' prior education health was reproductive adolescent in the SMP Negeri 2 Ampel Boyolali largely lacking as many as 71 students (50,7%). Knowledge students' after the adolescent reproductive health education in SMP 2 Ampel Boyolali well as most of the 72 students (51,4%). The results test Wilcoxon Signed Ranks Test via the media leaflet obtained p-value 0,000 <0,05 there are 55 students to increase knowledge. While the media audio visual obtained through p-value0,000 < 0,05 there are 39 students have increased knowledge. The results test Kolomogorov Smirnov obtained p-value 0,020 < 0,05. Conclusion: There is a difference in education health via media audio visual and leaflets to knowledge students about health reproductive of adolescents in SMP Negeri 2 Ampel Boyolali. Key words: Education health, media audiovisual, media leaflet